Analysis of the urban transport system to optimize the passenger travel time of the city of Puno-2018 - Chique Calderón, Boris Jaime (2020)
The objetive of the research was to analyze the system urban transport of the city of Puno, it is proposed an urban road infrastructure to have a road capacity according to the type of road and thus be able to optimize the passenger's travel time according to the mobility trend, mobility of destination origin according to areas, mobility of urban transport. The route of urban public transport routes was analyzed to determine the average speed and thus be able to know the travel times. The hypothesis that has been formulated is: with the analysis of the urban transport system, urban road infrastructure is proposed to optimize the passenger travel time of the city of Puno-2018, the mobility trend is analyzed according to destination origin, the mobility of the urban transport, public urban transport routes and urban road infrastructure. The research focused its methodology, under a quantitative approach, non-experimental design. A questionnaire was applied as an instrument for analysis; of which allowed to collect information and analyze the study variables and make correlations. The sample was made up of 384 passengers and 8 minibuses that provide service on the main urban public transport routes. As a result, the urban transport system of the city of Puno is concentrated due to the use of land in the downtown area, vehicular mobility has obstacles in the flow due to the use of the roadway as parking and that the roads exceed its capacity. road which does not optimize travel times in the city of Puno for which urban road infrastructure is required such as: land terminals, paving of roads, bus stops, declaring rigid areas the roads that are used by urban transport routes and implement an intelligent traffic management system at the main intersections of the city